ANALISIS HUBUNGAN PELAKSANAAN PROMOSI KESEHATAN DENGAN KUNJUNGAN IBU BALITA KE POSYANDU DI PUSKESMAS NANGGALO DAN PUSKESMAS LUBUK BUAYA KOTA PADANG TAHUN 2015 - Hilda Hidayat (Jurnal Riset Hesti Medan, 2018)
The role of health promotion is very important in anticipating the behavior of the public to know, willing and able to mobilize mothers to Posyandu. But, the process of behavioral change in society is not easy, it is seen at the Nanggalo Health Center which has a rate visit new mothers to Posyandu is 43.2% and highest 77.1% in Puskesmas Lubuk Buaya with a target of 80%. The research has done in February until August 2015 was conducted using qualitative research methods, the research location in Nanggalo Health Center and Lubuk Buaya Health Centre in Padang City. The qualitative data was collected using interview guideline to 6 informants, document analysis and observation. Qualitative data processing by triangulation. At Nanggalo and Lubuk Buaya Health Centre there is no technical rule, financial resources, and Region Budget Income and Health Operational Financial. At Nanggalo Health Centre, Health Promotion Officer as posyandu officer, and then at Lubuk Buaya Health Centre Health Promotion Officer as activity coordinator. Lubuk Buaya Posyandu stay at citizen home and facilities are available but in Nanggalo hasn’t. Partnership and empowerement Lubuk Buaya Health Centre run as expected compare Nanggalo Health Centre cause of that the mother to visit posyandu almost reach of target. Health Centre make technical rule and decision letter to hold posyandu training, and health promotion manual direction.Keywords : Analysis Health Promotion (Advocacy, Partnership, Community Empowerment), Visit Mother Toddler